2007
DOI: 10.1080/15572536.2007.11832547
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and ecology of myxomycetes in the high-elevation oak forests of Cerro Bellavista, Costa Rica

Abstract: Myxomycetes associated with a high-elevation (>3000 m) oak forest in the Talamanca Range of Costa Rica were studied for 7 mo. Field collections were supplemented with collections obtained from moist chamber cultures prepared with samples of bark and ground litter of Quercus costaricensis. Various microenvironmental parameters including pH, substrate moisture and diameter, height above the ground and canopy openness were recorded for each field collection, whereas macroenvironmental data for temperature and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…For example, previous studies have shown that some myxomycete species seem to be very substrate-specific (e.g., Stephenson et al 2008b; or largely influenced by environmental factors (e.g., Rojas and Stephenson 2007). This specificity is likely to have an effect on the macroecological characteristics of different assemblages.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…For example, previous studies have shown that some myxomycete species seem to be very substrate-specific (e.g., Stephenson et al 2008b; or largely influenced by environmental factors (e.g., Rojas and Stephenson 2007). This specificity is likely to have an effect on the macroecological characteristics of different assemblages.…”
Section: Introductionmentioning
confidence: 92%
“…This has generated a somewhat biased view of the distribution and ecology of myxomycetes in the Neotropics, since some macro-and microhabitats are underrepresented as an artifact of this restricted sampling. In spite of that, recent efforts have been made to alleviate this problem and studies of higher elevation areas in the Neotropics have also been carried out (e.g., Rodríguez-Palma et al 2005;Rojas and Stephenson 2007).…”
Section: Introductionmentioning
confidence: 98%
“…In addition, a highelevation ([3,000 m) oak forest in the Neotropics yielded several species that were the same as the species found in the Japanese subalpine, i.e. Cribraria mirabilis, C. piriformis, C. vulgaris, Lamproderma columbinum, Trichia botrytis and T. verrucosa (Rojas and Stephenson 2007). Thus, these myxomycetes were representative of an association of occurrence with cold climates, which may be favorable for the growth of certain myxomycetes.…”
Section: Discussionmentioning
confidence: 95%
“…In the present study, five autumnal species of Cribraria in the subalpine forest were different from the montane species and contributed increasing to subalpine species diversity. However, in the recent studies in the Neotropics (Rojas and Stephenson 2007;Lado and de Basanta 2008) those several species of Cribraria were found in high-elevation forests in mountains. It is not necessary to assume that subalpine species form widely distributed in biogeographical mountain element with typical coniferous forests.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation